2018
DOI: 10.3991/ijim.v12i5.8186
|View full text |Cite
|
Sign up to set email alerts
|

Automated Adaptive Mobile Learning System using Shortest Path Algorithm and Learning Style

Abstract: <p class="Abstract"><span>A directed graph represents an accurate picture of course descriptions for online courses through computer-based implementation of various educational systems. E-learning and m-learning systems are modeled as a weighted, directed graph where each node represents a course unit. The Learning Path Graph (LPG) represents and describes the structure of domain knowledge, including the learning goals, and all other available learning paths. In this paper, we propose a system prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…To describe the structure of domain knowledge, including the learning goals, and all other available learning paths, this study has proposed a learning path graph (LPG) inscribed in a system prototype that implements adaptive learning path algorithms. The proposed algorithms use students' information from their profiles and their learning style to improve academic performance within an m-learning system that provides a suitable course content sequence in a personalized manner [32]. Many investigations are devoted to analyzing the capabilities of mobile applications that can advance learning and develop students' professional skills.…”
Section: Discussionmentioning
confidence: 99%
“…To describe the structure of domain knowledge, including the learning goals, and all other available learning paths, this study has proposed a learning path graph (LPG) inscribed in a system prototype that implements adaptive learning path algorithms. The proposed algorithms use students' information from their profiles and their learning style to improve academic performance within an m-learning system that provides a suitable course content sequence in a personalized manner [32]. Many investigations are devoted to analyzing the capabilities of mobile applications that can advance learning and develop students' professional skills.…”
Section: Discussionmentioning
confidence: 99%
“…[34] P22 [35] them from the rest of the references in this document, we assigned them an identifier, as seen in Table 2. Concerning the years of publication of the selected studies, a variable frequency can be observed regarding the number of publications, highlighting the years 2012, 2015 2017, and 2019, as seen in Figure 2.…”
Section: P1 [14] P2mentioning
confidence: 99%
“…Furthermore, Karas et al [11] proposed a method to help students to form the knowledge network model and analysis of KG. In another study, Alshalabi et al [12] proposed an adaptive learning path algorithm by analyzing the structure of domain-specific knowledge to improve the academic performance of students. Moreover, Lv et al [13] solved the lack of logic knowledge relations on the semantic level using the nursing KG of the curriculum model.…”
Section: State Of the Artmentioning
confidence: 99%